Synthesis of Planar Filters Using Defected Ground Structure Miniaturized Hairpin Resonators - Nedelchev, M.; Kolev, A. (Engineering, Technology & Applied Science Research, 2019)
This paper presents an effective technique to suppress the spurious passbands in planar filters by using defected ground structure (DGS) resonators etched in the ground plane. The proposed miniaturized hairpin DGS slot resonator is researched in terms of its resonance frequency, corresponding coupling topologies, and filter design. The resonator and the topologies of coupled DGS resonators are simulated in a fullwave electromagnetic (EM) simulator. Using a curve-fitting technique, useful design formulas are proposed for filter synthesis. Using the synthesis procedure, a 3rd order filter design is simulated, manufactured and measured. The insertion loss of -3dB in the passband of 280MHz is observed, while the suppression of the spurious passbands up to 12GHz is more than 24dB.